Dynamic network biomarker analysis and system pharmacology methods to explore the therapeutic effects and targets of Xiaoyaosan against liver cirrhosis. (10th August 2022) - Lu, Yiyu; Li, Meiyi; Zhou, Qianmei; Fang, Dongdong; Wu, Rong; Li, Qingya; Chen, Luonan; Su, Shibing
Abstract: Ethnopharmacological relevance: Xiaoyaosan is a traditional Chinese herbal formula that has long been used to treat liver cirrhosis, liver failure, and hepatocarcinoma (HCC). However, little is known about its mechanism of action and targets in treating chronic liver disease. Aim of the study : This study aimed to detect the critical transition of HCC progression and to explore the regulatory mechanism and targets of Xiaoyaosan treating liver cirrhosis (cirrhosis) using integrative medicinal research involving system biology and pharmacology. Materials and methods: We recruited chronic liver disease participants to obtain gene expression data and applied the dynamic network biomarker (DNB) method to identify molecular markers and the critical transition. We combined network pharmacology and DNB analysis to locate the potential DNBs (targets). Then we validated the DNBs in the liver cirrhosis rat models using Xiaoyaosan treatment. The expression of genes encoding the four DNBs, including Cebpa, Csf1, Egfr, and Il7r, were further validated in rat liver tissue using Western blot analysis. Results: We found EGFR, CEBPA, Csf1, Ccnb1, Rrmm2, C3, Il7r, Ccna2, and Peg10 overlap in the DNB list and Xiaoyaosan-Target-Disease (XTD) network constructed using network pharmacology databases. We investigated the diagnostic ability of each member in the DNB cluster and found EGFR, CEBPA, CSF1, and IL7R had high diagnostic abilities with AUC >0.7 and P -value < 0.05. We validated these findings in rats and found that liver function improved significantly and fibrotic changes were relieved in the Xiaoyaosan treatment group. The expression levels of CSF1 and IL7R in the Xiaoyaosan group were significantly lower than those in the cirrhosis model group. In contrast, CEBPA expression in the Xiaoyaosan group was significantly higher than that in the cirrhosis model group. The expression of EGFR in the Xiaoyaosan group was slightly decreased than in the model group but not significantly. Conclusion: Using the DNB method and network pharmacology approach, this study revealed that CEBPA, IL7R, EGFR, and CSF1 expression was remarkably altered in chronic liver disease and thus, may play an important role in driving the progression of cirrhosis. Therefore, CEBPA, IL7R, EGFR, and CSF1 may be important targets of Xiaoyaosan in treating cirrhosis and can be considered for developing novel therapeutics. Graphical abstract: Image 1